How Does AI Improve Surgical Planning and Simulation? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2016)
Artificial intelligence (AI) is no longer a concept confined to science fiction; it is a transformative force in numerous fields, including medicine. Within ...
Keywords: AI in Surgery and Robotics; Improve; Surgical; Planning; Artificial Intelligence; Machine Learning